Analisis Kesulitan Siswa dalam Mengimplementasikan Pembelajaran Tematik di SD Negeri No. 101117 Mondang Baringin - Yuyun Niptah Rambe; Desy Ratna Sari Siregar; Rama Nida Siregar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to identify the difficulties students face in implementing thematic learning in elementary schools. The type of research employed is quantitative research, utilizing a descriptive data analysis method to examine the identified issues. The subjects of this study are the teachers and fourth-grade students of SD Negeri No. 101117 Mondang Baringin.Thematic learning is often referred to as integrated learning because it serves as a model that uses specific themes to link multiple subjects, thereby providing a more meaningful experience for students. The difficulties students encounter in implementing this thematic approach are caused by several factors, including both internal and external factors. Ultimately, the objective of this research is to determine the specific obstacles students face in the implementation of thematic learning